Calcium-sensing receptor gene polymorphisms in patients with calcium urolithiasis: a systematic review. (September 2014) - Besiroglu, Huseyin; Sahin, Suleyman; Otunctemur, Alper; Ozbek, Emin
Abstract Background: Calcium-sensing receptor gene (CaSR) might be a strong component of the complex genetic background regulating calcium excretion and stone formation in kidney. The polymorphisms in different parts of the gene could be associated with calcium stone formation. Objective: The individual studies indicate a correlation between CaSR gene polymorphisms and urolithiasis but not sufficient to draw a precise result. We aimed to search literature to come to a reliable conclusion through a systematic review. Materials and methods: We have serached individiual studies regarding the issue and high quality reviews. We assessed all the studies to draw a conclusion. Conclusion: The genetic background of the neprolithiasis is an interesting issue deserving to be disscussed on. Regading genes of which, CaSR gene polymorphisms is the leading one, are studied in many individual studies but they are not sufficient to have a precise conclusion. Well-oriented and documented, phenotypically homogenous large cohort studies are needed for further evaluation.